AIP mutations in Brazilian patients with sporadic pituitary adenomas: a single-center evaluation. Issue 8 (November 2017) - Araujo, Paula Bruna; Kasuki, Leandro; de Azeredo Lima, Carlos Henrique; Ogino, Liana; Camacho, Aline H S; Chimelli, Leila; Korbonits, Márta; Gadelha, Monica R
Abstract : Aryl hydrocarbon receptor-interacting protein ( AIP ) gene mutations ( AIPmut ) are the most frequent germline mutations found in apparently sporadic pituitary adenomas (SPA). Our aim was to evaluate the frequency of AIPmut among young Brazilian patients with SPA. We performed an observational cohort study between 2013 and 2016 in a single referral center. AIPmut screening was carried out in 132 SPA patients with macroadenomas diagnosed up to 40 years or in adenomas of any size diagnosed until 18 years of age. Twelve tumor samples were also analyzed. Leukocyte DNA and tumor tissue DNA were sequenced for the entire AIP -coding region for evaluation of mutations. Eleven (8.3%) of the 132 patients had AIPmut, comprising 9/74 (12%) somatotropinomas, 1/38 (2.6%) prolactinoma, 1/10 (10%) corticotropinoma and no non-functioning adenomas. In pediatric patients (≤18 years), AIPmut frequency was 13.3% (2/15). Out of the 5 patients with gigantism, two had AIPmut, both truncating mutations. The Y268* mutation was described in Brazilian patients and the K273Rfs*30 mutation is a novel mutation in our patient. No somatic AIP mutations were found in the 12 tumor samples. A tumor sample from an acromegaly patient harboring the A299V AIPmut showed loss of heterozygosity. In conclusion, AIPmut frequency in SPA Brazilian patients is similar to other populations. Our study identified two mutations exclusively found in Brazilians and also shows, for the first time, loss of heterozygosity in tumor DNA from an acromegaly patient harboring the A299V AIPmut . Our findings corroborate previous observations that AIPmut screening should be performed in young patients with SPA.